2015
DOI: 10.1021/acscatal.5b02325
|View full text |Cite
|
Sign up to set email alerts
|

Bimetal–Organic Framework Self-Adjusted Synthesis of Support-Free Nonprecious Electrocatalysts for Efficient Oxygen Reduction

Abstract: The development of low-cost catalysts with oxygen reduction reaction (ORR) activity superior to that of Pt for fuel cells is highly desirable but remains challenging. Herein, we report a bimetalorganic framework (bi-MOF) self-adjusted synthesis of support-free porous Co-N-C nanopolyhedron electrocatalysts by pyrolysis of Zn/Co bi-MOF without any post-treatments. The presence of initial Zn forms a spatial isolation of Co which suppresses its sintering during pyrolysis and the Zn evaporation also promotes the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
286
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 457 publications
(300 citation statements)
references
References 50 publications
(110 reference statements)
13
286
1
Order By: Relevance
“…By means of annealing under a controlled temperature and atmosphere, the organic units can be transformed into heteroatom-doped carbon materials, while metal-containing units are simultaneously converted into the corresponding transition-metal-based NPs supported on the as-formed carbon substrate. [24,38,41,42,44,53] More importantly, the advancement of chemical modification allows the precise manipulation of the component for the resultant composites. [41] From the view of composition, MOF-derived composites could offer strong synergistic effects between the carbon framework and metal component, which is highly preferable in enhancing electrocatalytic performance.…”
Section: Component Manipulationmentioning
confidence: 99%
See 4 more Smart Citations
“…By means of annealing under a controlled temperature and atmosphere, the organic units can be transformed into heteroatom-doped carbon materials, while metal-containing units are simultaneously converted into the corresponding transition-metal-based NPs supported on the as-formed carbon substrate. [24,38,41,42,44,53] More importantly, the advancement of chemical modification allows the precise manipulation of the component for the resultant composites. [41] From the view of composition, MOF-derived composites could offer strong synergistic effects between the carbon framework and metal component, which is highly preferable in enhancing electrocatalytic performance.…”
Section: Component Manipulationmentioning
confidence: 99%
“…[58,60] For instance, in order to fabricate N-doped MOF-derived materials, zeolitic imiazolate frameworks (ZIFs), a subclass of MOFs composed of tetrahedrally coordinated transition metal ions (e.g., Zn, Fe, Co, Cu) and imidazolate (IM) ligands, are frequently utilized as the precursor and/or template because of their high N content and other preferred properties, such as large surface area and uniform particle size. [24,33,34,36,[38][39][40][41]44,53,[64][65][66][67][68][69] Recently, You et al reported the conversion of ZIF-67 (Co(MIM) 2 , MIM = methylimidazole) to Co-and N-doped carbon (CoNC) via direct pyrolysis, producing a N-doped material with high N content. [39] Similarly, Chen and co-workers studied porous carbon materials derived from a series of bimetallic ZIFs (BMZIFs), which are based on ZIF-8 and ZIF-67 with varied Zn/Co ratio.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
See 3 more Smart Citations